PERANCANGAN PENJADWALAN FLOWSHOP MENGGUNAKAN PARTICLE SWARM OPTIMIZATION UNTUK MEMINIMASI NUMBER OF TARDY JOBS - Rahmi Maulidya; Docki Saraswati; Divani Vania (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
This paper propose an algorithm for general flowshop scheduling problems using Particle Swarm Optimization that can minimize number of tardy jobs. The algorithm is illustrated in a case study from the heavy equipment manufacturing industry. The proposed algorithm based on Particle Swarm Optimization algorithm developed by Tasgetiren using routing symbols, combined with the characteristic of its production. The jobs would be process in first work station using Particle Swarm Optimization approaches, for 2nd until 11th works stasion using first come first served rules and earliest due date rules for assembly’s works station.